Analisis Faktor-Faktor Penyebab Niat Wanita Pekerja Seks (WPS) Yang Menderita IMS Berperilaku Seks Aman (Safe Sex) Dalam Melayani Pelanggan - Arifianti, Nur Azmi; P, Harbandinah; P, Priyadi Nugraha (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2008)
Background: WHO estimated that there are 350 million new cases of Sexual Transmitted Infectious (STI) in developing countries. In Indonesia, gonorrhea infection was the highest among STI infections. Tegal district is one district in Central Java province which also had a higher rate of STI infection. This study aims to analyze the intention of female sex workers to have a safe sex with their clients.Method: This research was a cross sectional study and exploratory survey research employed quantitative and qualitative approach. There were 64 STI sufferers from monthly screening (April 2008) were involved in this study. Chi Square test and logistic regression was employed to analyze the result.Result: Bivariate analysis showed perceived severity of the disease (p=0,016) and self efficacy (p=0,001) were related to safe sex intention whilst perceived risk (p=0,731) and effective response (p=0,066) were not statistically correlate to safe sex intention. Multivariate analysis resulted self efficacy was the most influence factor on safe intention. This study recommends improving health education for female sex workers especially about STI and condom use. One hundred percent condom use inside and outside localization should be intensively implemented in order to reduce STI occurrence among female sex workers.Keyword : safe sex intention, female sex worker, sexual transmitted infectious